Holding solution pH and composition consistently improve vase life of rose, lily and gerbera - Othman, Yahia A.; A’saf, Tala S.; Al-Ajlouni, Malik G.; Hani, Muayyad Bany; Hilaire, Rolston St. (Journal of Phytology, 2023)
We assessed the influence of postharvest pulsing solutions pH and composition on cut flower quality of rose (Rosa hybrida cvs. Avalanche and Black Magic), gerbera (Gerbera jamesonii cv. Beaudine) and lily (Lilium × elegans cv. Fangio) under room (20±2 °C) and cold storage (4±1 °C) conditions. Cut flowers were placed in different acidic (pH, 3.5 - 4) or basic (pH, 7.0 - 7.5) preservative solutions containing water, sugar 5% (flower food), 100 mg/L silver nitrate (AgNO3 act as a bactericide), or a commercial product (2% sugar + bactericide and fungicide). Acidic solutions had higher or similar (never lower) vase life at both room and cold storage conditions and across species. In addition, vase life was 3-4 times longer in cold storage when compared to room conditions. Leaf chlorophyll concentrations for rose and lily were inconsistent or not significant across the species at both conditions (room and cold storage). The commercial preservative solution consistently and significantly had higher vase life than water for all tested cut flower species and under both room and cold storage environments. AgNO3 ranked second in terms of vase life enhancement. Overall, the use of only flower food (sugar) or bactericide (AgNO3) had a positive impact on vase life but only the combined use of a preservative substance (specifically at pH, 3.5 - 4.0) consistently guaranteed a high cut flower quality across flower species.